Exploring the Diversity and Novelty of Toxin Genes in Naja sumatrana, the Equatorial Spitting Cobra from Malaysia through De Novo Venom-Gland Transcriptomics - Chong, Ho Phin (Toxins (Basel), 2019)
The equatorial spitting cobra, Naja sumatrana, is a distinct species of medically important venomous snakes, listed as WHO Category 1 in Southeast Asia. The diversity of its venom genes has not been comprehensively examined, although a few toxin sequences annotated to Naja sputatrix were reported previously through cloning studies. To investigate this species venom genes’ diversity, de novo venom-gland transcriptomics of N. sumatrana from West Malaysia was conducted using next-generation sequencing technology. Genes encoding toxins represented only 60 of the 55,396 transcripts, but were highly expressed, contributing to 79.22% of total gene expression (by total FPKM) in the venom-glands. The toxin transcripts belong to 21 families, and 29 transcripts were further identified as full-length. Three-finger toxins (3FTx) composed of long, short, and non-conventional groups, constituted the majority of toxin transcripts (91.11% of total toxin FPKM), followed by phospholipase A(2) (PLA(2), 7.42%)—which are putatively pro-inflammatory and cytotoxic. The remaining transcripts in the 19 families were expressed at extremely low levels. Presumably, these toxins were associated with ancillary functions. Our findings unveil the diverse toxin genes unique to N. sumatrana, and provide insights into the pathophysiology of N. sumatrana envenoming.